Cellular functions and biomedical applications of circular RNAs - Zhang Zheyu; Wang Zefeng (Acta Biochimica et Biophysica Sinica)
Circular RNAs (circRNAs) have emerged as a large class of stable and conserved RNAs that are derived primarily from back-splicing of pre-mRNAs and expressed in a cell- and tissue-specific fashion. Recent studies have indicated that a subset of circRNAs may undergo translation through cap-independent pathways mediated by internal ribosome entry sites (IRESs), m6A modifications, or IRES-like short elements. Considering the stability and low immunogenicity of circRNAs, in vitro transcribed circRNAs hold great promise in biomedical applications. In this review, we briefly discuss the noncoding and coding functions of circRNAs in cells, as well as the methods for the in vitro synthesis of circRNAs and current advances in the applications of circRNAs in biomedicine.